Magic Mike [videorecording (DVD)] - Soderbergh, Steven, 1963-; Soderbergh, Steven, 1963-; Carolin, Reid, 1982-; McConaughey, Matthew, 1969-; Tatum, Channing; Pettyfer, Alex, 1990-; Horn, Cody, 1988-; Munn, Olivia, 1980-; Bomer, Matthew, 1977-; Manganiello, Joe; Rodriguez, Adam, 1975- (Warner Bros. Entertainment, Inc., 2012)
Mike, an experienced stripper, takes a younger performer called The Kid under his wing and schools him in the arts of partying, picking up women, and making easy money.